2007
DOI: 10.1186/1472-6963-7-129
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare in schizophrenia: effectiveness and progress of a redesigned care network

Abstract: Background: The aim of this study was designed to investigate the care-effectiveness of different healthcare models for schizophrenic patients and the impact of it on caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 37 publications
0
36
1
1
Order By: Relevance
“…This clinical outcome could be attributed to the lack of rehabilitation facilities and community-based therapeutic resources in our setting. The implication is that available family social support needs to be backed up by efforts at psychosocial rehabilitation and family psychoeducation, in order to enhance the clinical outcome [10,12,[17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This clinical outcome could be attributed to the lack of rehabilitation facilities and community-based therapeutic resources in our setting. The implication is that available family social support needs to be backed up by efforts at psychosocial rehabilitation and family psychoeducation, in order to enhance the clinical outcome [10,12,[17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…The indications are that severity of psychosis is associated with caregiver burden, perception of unmet need for care and dissatisfaction with services. This later line of inquiry is important because interventions from the perspective of quality of care have been shown to have a beneficial impact on severity of psychopathology [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…While some questionnaires that measure QOL have been developed for specific diseases 34,35) , the WHO-QOL is generic and can be used on all people 36) . In the parsimonious model of regression analysis, we found nurses, life event and hypnotic drug use could predict GHQ, and GHQ could predict the QOL.…”
Section: Psychological Morbidity Predicts Qol Of Health Care Workersmentioning
confidence: 99%
“…Women have been reported by several epidemiological studies to have a higher prevalence of psychological morbidity 7,27,28,31,32) . In this study, we found higher prevalence of psychological morbidity in nurses in high strain jobs at baseline and in nurses working in job with greater psychological demand at follow up.…”
Section: Discussionmentioning
confidence: 99%